Public Health in Developing Countries - Challenges and Opportunities 2020
DOI: 10.5772/intechopen.92090
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Science of Indigenous Health System: Key to Sustainable Collaborations

Abstract: Most of the health systems in developing countries are dysfunctional and hardly responsive to the needs and demands of patients. Access to a plural healthcare system and reports of patients abandoning western medicine for indigenous medicine are signs of nonresponsive health system. The major contributing factors are the failures of the allopathic health system to recognize that indigenous medicine is a living and practised science, with its own philosophy, beliefs and practices developed over centuries. Indig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…This more frequently framed around people of the so-called ‘charismatic churches’ or the Pentecostal churches in South Africa, which are known as ‘Bazalwane’ or the ‘Born again’ Christians. This finding is supported by a study by Nemutandani, Hendrick and Mulaudzi ( 2020 ) who found that the introduction of Euro-western culture, practice and religious beliefs, such as the Christian faith, dominated and disregarded the indigenous knowledge systems.…”
Section: Discussionmentioning
confidence: 66%
“…This more frequently framed around people of the so-called ‘charismatic churches’ or the Pentecostal churches in South Africa, which are known as ‘Bazalwane’ or the ‘Born again’ Christians. This finding is supported by a study by Nemutandani, Hendrick and Mulaudzi ( 2020 ) who found that the introduction of Euro-western culture, practice and religious beliefs, such as the Christian faith, dominated and disregarded the indigenous knowledge systems.…”
Section: Discussionmentioning
confidence: 66%